Adaptive periodicity in the infectivity of malaria gametocytes to mosquitoes. Issue 1888 (10th October 2018) - Schneider, Petra; Rund, Samuel S. C.; Smith, Natasha L.; Prior, Kimberley F.; O'Donnell, Aidan J.; Reece, Sarah E.
Abstract : Daily rhythms in behaviour, physiology and molecular processes are expected to enable organisms to appropriately schedule activities according to consequences of the daily rotation of the Earth. For parasites, this includes capitalizing on periodicity in transmission opportunities and for hosts/vectors, this may select for rhythms in immune defence. We examine rhythms in the density and infectivity of transmission forms (gametocytes) of rodent malaria parasites in the host's blood, parasite development inside mosquito vectors and potential for onwards transmission. Furthermore, we simultaneously test whether mosquitoes exhibit rhythms in susceptibility. We reveal that at night, gametocytes are twice as infective, despite being less numerous in the blood. Enhanced infectiousness at night interacts with mosquito rhythms to increase sporozoite burdens fourfold when mosquitoes feed during their rest phase. Thus, changes in mosquito biting time (owing to bed nets) may render gametocytes less infective, but this is compensated for by the greater mosquito susceptibility.